Educational Planning, Administration and Evaluation in Fourth Five Year Plan (1969-74) - Education Division Planning Commission (Education Division Planning Commission Government of India, 1968)
This summary synthesizes the findings of the Working Party on Educational Planning, Administration, and Evaluation and the Education Commission in the context of the Fourth Five-Year Plan (1969–74). It highlights major weaknesses in existing educational planning and administration, including excessive emphasis on financial targets, weak coordination, limited teacher involvement, and inadequate administrative capacity. The reports advocate comprehensive and decentralized planning, strengthened institutional development plans, systematic in-service training, and the creation of a National Staff College to professionalize educational administration. Emphasis is placed on flexibility, continuous evaluation, research integration, and improved resource allocation to ensure qualitative improvements in education. Collectively, the recommendations aim to transform educational administration from a maintenance-oriented system into a dynamic, development-focused framework aligned with national socio-economic goals.
Report of Working Party on Educational Planning, Administration and Evaluation
Education Division Planning Commission Government of India New Delhi September, 1968
Keywords: Educational Planning; Educational Administration; Fourth Five-Year Plan; Decentralized Planning; Institutional Development Plans; In-Service Training; National Staff College; Administrative Reforms; Teacher Participation; Programme Evaluation; Curriculum Flexibility; Education Financing